Teaching peace through popular culture - Finley, Laura L. (Peace education., 2023)
"Drawing from many disciplinary areas, this edited volume illustrates the many ways that popular culture can be used to teach peace and justice. Chapters address such topics as teaching about racism, domestic violence, structural violence, conflict analysis, decolonization, critiques of capitalism, and peacebuilding, showing how different forms of popular culture can be utilized to enhance student learning. Contributors provide both theoretical backgrounds and concrete lessons using TV, film, music, graphic novels, and more"--